Implementasi Metode Al-Miftah Lil Ulum Dalam Meningkatkan Kemampuan Membaca Kitab Kuning Santri Nurul Huda Pakamban Laok Pragaan Sumenep - Kamelia, Andini; El-Faradis, Fayruzah (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Nurul Huda Islamic Boarding School is one of the huts that applies the Al-Miftah Lil Ulum method in teaching the yellow book to its students. Where the Al-Miftah Lil Ulum method is a practical method in reading and mastering the yellow book which is the work of Ustadz Qusyairi Ismail. The study of the yellow book not only educates students about Islamic religious education, but also seeks to help students master, understand, and practice Islamic teachings as a source of motivation in education for progress and development in every field of life. This researcher uses a qualitative field research approach. And data collection methods using interviews, observation and documentation. For the validity of the data using source triangulation and triangulation techniques to compare the results of interviews, observations and documentation.